2019
DOI: 10.1109/access.2019.2927075
|View full text |Cite
|
Sign up to set email alerts
|

CharBot: A Simple and Effective Method for Evading DGA Classifiers

Abstract: Domain generation algorithms (DGAs) are commonly leveraged by malware to create lists of domain names which can be used for command and control (C&C) purposes. Approaches based on machine learning have recently been developed to automatically detect generated domain names in real-time. In this work, we present a novel DGA called CharBot which is capable of producing large numbers of unregistered domain names that are not detected by state-of-the-art classifiers for real-time detection of DGAs, including the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…To the best of our knowledge, this is only work which can capture generated domain names with this level of fidelity, and as such, can be instrumental in tracking and detecting botnets via DNS traffic. Furthermore, we have found that Helix is robust to the camouflage evasion techniques [2,12,18] compared a state of the art DGA classifier. Lastly, Helix is practical because autoencoders are trained in an unsupervised manner, meaning that there is no need for manual labeling.…”
Section: Candcmentioning
confidence: 98%
See 1 more Smart Citation
“…To the best of our knowledge, this is only work which can capture generated domain names with this level of fidelity, and as such, can be instrumental in tracking and detecting botnets via DNS traffic. Furthermore, we have found that Helix is robust to the camouflage evasion techniques [2,12,18] compared a state of the art DGA classifier. Lastly, Helix is practical because autoencoders are trained in an unsupervised manner, meaning that there is no need for manual labeling.…”
Section: Candcmentioning
confidence: 98%
“…Hi master, what should I do now? Figure 1: An illustration of the process which an attacker performs in order to connect a botnet to a C&C. [16,19] [Helix ] generated ones [2,12,18]. Therefore, there is a need for a stronger representation of domain names, one which can capture both the underlying DGA and the presence of camouflage attacks.…”
Section: Candcmentioning
confidence: 99%
“…This paper uses raw data collected from three sources: Alexa, Qname, and Bambenek. The data sets utilized are the same as those used in [8].…”
Section: Raw Datamentioning
confidence: 99%
“…Bambenek 2 offers a daily feed of domains generated by reverse engineering known families of malware. One million different DGA domains were collected over the course of three days to construct a malicious data set [8].…”
Section: Raw Datamentioning
confidence: 99%
See 1 more Smart Citation